2023
DOI: 10.3390/ijms24043616
|View full text |Cite
|
Sign up to set email alerts
|

AQP1 in the Gastrointestinal Tract of Mice: Expression Pattern and Impact of AQP1 Knockout on Colonic Function

Abstract: Aquaporin 1 (AQP1) is one of thirteen known mammalian aquaporins. Its main function is the transport of water across cell membranes. Lately, a role of AQP has been attributed to other physiological and pathological functions including cell migration and peripheral pain perception. AQP1 has been found in several parts of the enteric nervous system, e.g., in the rat ileum and in the ovine duodenum. Its function in the intestine appears to be multifaceted and is still not completely understood. The aim of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…In the peripheral nervous system, AQP1 expression is observed in a subset of primary sensory neurons located in the dorsal root and nodose ganglia of mice [ 48 ]. Furthermore, AQP1 is present in enteric neurons of both mice and rats, indicating its role in the gastrointestinal nervous system, where it likely contributes to fluid transport and neuronal function [ 49 ]. It was also described in the human trigeminal system [ 50 ].…”
Section: Aquaporins In the Cnsmentioning
confidence: 99%
“…In the peripheral nervous system, AQP1 expression is observed in a subset of primary sensory neurons located in the dorsal root and nodose ganglia of mice [ 48 ]. Furthermore, AQP1 is present in enteric neurons of both mice and rats, indicating its role in the gastrointestinal nervous system, where it likely contributes to fluid transport and neuronal function [ 49 ]. It was also described in the human trigeminal system [ 50 ].…”
Section: Aquaporins In the Cnsmentioning
confidence: 99%
“…The expression of AQP1 in the villi and the crypt of enterocytes otherwise suggests its role in absorption and secretion . Several studies have demonstrated that the highest level of AQP1 in the gastrointestinal tract was observed in the small intestine, and AQP1 expression was associated with the intestinal wall thickness and other aspects of intestinal function . A recent study found that DEHP exposure induced renal damage through targeted inhibition of AQPs, especially AQP1 .…”
Section: Introductionmentioning
confidence: 99%
“…17 Several studies have demonstrated that the highest level of AQP1 in the gastrointestinal tract was observed in the small intestine, and AQP1 expression was associated with the intestinal wall thickness and other aspects of intestinal function. 18 A recent study found that DEHP exposure induced renal damage through targeted inhibition of AQPs, especially AQP1. 19 Although the function of AQP1 in the intestine appears to be diverse, the role of AQP1 in DEHP-induced intestinal inflammation and damage is not completely established.…”
Section: Introductionmentioning
confidence: 99%
“…2020 ). AQP-1 has been identified in the gastrointestinal tract from the oesophagus to the colon, and in glial cells and neurons in the enteric nervous system ( Volkart et al. 2023 ).…”
mentioning
confidence: 99%
“…AQPs are present in almost all living systems and viruses (Ishibashi et al 2020). AQP-1 has been identified in the gastrointestinal tract from the oesophagus to the colon, and in glial cells and neurons in the enteric nervous system (Volkart et al 2023). Although the exact role of AQP-1 in the enteric nervous system remains unclear, it has been linked to pathological mechanisms such as pain https://doi.org/10.17221/111/2023-VETMED sensation, inflammatory responses, hypoxic conditions, and diabetes (Wagner et al 2022).…”
mentioning
confidence: 99%